1995
DOI: 10.1021/jm00023a005
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Backbone Structure between Angiotensin II Agonists and Type I Antagonists

Abstract: Type I angiotensin II antagonists with O-methyl-L-homoserine [HSer(gamma-OMe)] and delta-methoxy-L-norvaline [Nva(delta-OMe)] at position 8 have been prepared by the solid-phase method, purified by reverse-phase HPLC, and bioassayed in the rat uterus, and their backbone conformational properties were investigated by nuclear Overhauser effect (NOE) spectroscopy. [Sar1,HSer-(gamma-OMe)8]ANGII, [HSer(gamma-OMe)8]ANGII, [Des1,HSer(gamma-OMe)8]ANGII, [Sar1,Nva(delta-OMe)8]-ANGII, and [Des1,Nva(delta-OMe)8]ANGII had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0
2

Year Published

1996
1996
2011
2011

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 15 publications
(35 reference statements)
1
18
0
2
Order By: Relevance
“…In 1994, a model of AII based on NMR studies using 2D ROESY techniques in receptor simulating environments has been developed which involves an aromatic ring cluster and consequently a charge relay system formed from the triad of amino acids Tyr4-His6-Phe8 was suggested [52].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 1994, a model of AII based on NMR studies using 2D ROESY techniques in receptor simulating environments has been developed which involves an aromatic ring cluster and consequently a charge relay system formed from the triad of amino acids Tyr4-His6-Phe8 was suggested [52].…”
Section: Discussionmentioning
confidence: 99%
“…Comparative nuclear magnetic resonance studies of the backbone structure between peptide agonists and antagonists have shown that agonists display ring clustering and form a charge relay system [53] Such clustering is also present to the competitive antagonist [Tyr(OMe)4]AII (sarmesin) which lacks the potential of the charge relay system and the form of the tyrosinate anion which is a strict requirement for agonist activity in the proposed model [54,55]. In addition, the proposed conformation of AII and sarmesin overlay the non-peptide AII receptor antagonist losartan and its analogues when molecular modeling techniques and superimposition studies are applied [28].…”
Section: Discussionmentioning
confidence: 99%
“…One possible explanation for the extremely low receptor-binding affinity of TRI 'agonists' is provided by comparative structural studies, which have indicated that precise backbone turn formation is essential for the agonist activity of both BK [21] and AT II [22]. Antagonists, however, may adopt a more extended solution conformation [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…[11,12,13] Based on the molecular characterization of commercial SARTANs, synthetic peptidic and non-peptidic analogs, a new avenue was explored in an attempt to design and synthesize novel AT 1 antagonists. [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] Thus, MMK analogs have been synthesized to possess pyrrolidinone as template instead of biphenyltetrazole segment. [29,30] The lack of significant activity of the synthetic molecules as AT 1 antagonists led us to test them as anti-inflammatory drugs since it is well known from the literature that pyrrolidinone analogs have such a property.…”
Section: Introductionmentioning
confidence: 99%